A Combination System of p-Toluenesulfonic Acid and Acetic Acid for the Hydration of Alkynes - Liu, Haixuan; Wei, Yunyang; Cai, Chun (Synlett, 2016)
A simple combination system of p-toluenesulfonic acid/acetic acid has been developed for efficient hydration of alkynes. The corresponding ketones can be obtained in good to excellent yields under mild conditions. The mechanism of the reaction was disclosed unambiguously which was a stepwise process (addition and then hydrolysis). Furthermore, this system was proved to be powerful that has the potential to be used to synthesize vinyl 4-methylbenzenesulfonates.
Keywords: hydration; alkynes; ketones; hydrolysis; vinyl sulfonates